Determinants of Student Research Quality in Madrasah Aliyah: Student Characteristics, School Environment, and Learning Process - Iqbal, Muhammad; Irfan, Ahmad Zainul; Muzakkir, Muzakkir; Anam, Khaerul (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Student research programs in Madrasah Aliyah (MA) have been developed to strengthen scientific literacy and higher-order thinking skills, yet the quality of student research outputs remains uneven. This study examined the effects of student characteristics, school environment, and learning process on perceived student research quality, while also testing the mediating role of learning process. A quantitative associative-predictive design was employed involving 67 students from MAN IC Lombok Timur who had conducted research. Data were collected through a five-point Likert questionnaire and analyzed using PLS-SEM. The results showed that student characteristics had the strongest positive effect on perceived research quality (β = 0.611; p < 0.001), followed by school environment (β = 0.310; p = 0.018). School environment also significantly predicted learning process (β = 0.673; p < 0.001), whereas learning process did not significantly affect perceived research quality (β = −0.001; p = 0.994) and did not mediate the effects of the two predictors. These findings indicate that students’ academic self-efficacy, intrinsic motivation, self-regulation, and supportive school climate are associated with higher perceived research quality. At the same time, the non-significant role of learning process suggests that general classroom practices may not adequately capture the research-specific mentoring needed to support student research. The findings should be interpreted in light of the study’s self-reported and cross-sectional design.